URANS simulations of an axisymmetric submarine hull undergoing dynamic sway. (15th January 2019) - Doyle, R.; Jeans, T.L.; Holloway, A.G.L.; Fieger, D.
Abstract: A computational study of the flow over an axisymmetric submarine hull undergoing unsteady maneuvers is presented. The computational model is based on the Unsteady Reyonolds-Averaged Navier-Stokes equations, solved in body fixed coordinates using the Wilcox two-equation turbulence model. Static drift and dynamic sway simulations are performed on a hull geometry with a slenderness ratio of 8.5 and Reynolds number of 3.1 million, in strut-supported and unsupported configurations. Simulation results are compared with Horizontal Planar Motion Mechanism experiments at two reduced frequencies, k = 0.12 and k = 0.03 . Simulated results for a strut supported hull are compared with experimental values to estimate simulation accuracy for static drift and dynamic sway. Simulation results for an unsupported hull demonstrate significant hysteresis of the hydrodynamic forces at k = 0.12, while at k = 0.03 the lateral force and yawing moment collapse towards the quasi-steady limit. Dynamic forces are decomposed in terms of the inviscid added mass and a viscous component which cannot be accounted for by the quasi-steady assumption and is attributed to flow history effects. The effect of flow history is further shown by visualisations of the wake vorticity. Finally, it is demonstrated that the presence of the support strut results in significant interference effects in all cases. Highlights: Unsteady CFD simulations of a maneuvering submarine hull have been conducted. Simulated forces and moments are compared to the experimental results. The forces demonstrate hysteresis which cannot be modeled by quasi-steady methods. This hysteresis is believed to be due to motion history effects in the flow. The interference effects of the experimental support struts are examined.